The transcription factor GATA4 promotes myocardial regeneration in neonatal mice - Malek Mohammadi, Mona (EMBO Mol Med, 2017)
Heart failure is often the consequence of insufficient cardiac regeneration. Neonatal mice retain a certain capability of myocardial regeneration until postnatal day (P)7, although the underlying transcriptional mechanisms remain largely unknown. We demonstrate here that cardiac abundance of the transcription factor GATA4 was high at P1, but became strongly reduced at P7 in parallel with loss of regenerative capacity. Reconstitution of cardiac GATA4 levels by adenoviral gene transfer markedly improved cardiac regeneration after cryoinjury at P7. In contrast, the myocardial scar was larger in cardiomyocyte‐specific Gata4 knockout (CM‐G4‐KO) mice after cryoinjury at P0, indicative of impaired regeneration, which was accompanied by reduced cardiomyocyte proliferation and reduced myocardial angiogenesis in CM‐G4‐KO mice. Cardiomyocyte proliferation was also diminished in cardiac explants from CM‐G4‐KO mice and in isolated cardiomyocytes with reduced GATA4 expression. Mechanistically, decreased GATA4 levels caused the downregulation of several pro‐regenerative genes (among them interleukin‐13, Il13) in the myocardium. Interestingly, systemic administration of IL‐13 rescued defective heart regeneration in CM‐G4‐KO mice and could be evaluated as therapeutic strategy in the future.